Microphone Array Post-Processor Using Instantaneous Direction of Arrival - Tashev, Ivan; Acero, Alex (Proceedings of International Workshop on Acoustic, Echo and Noise Control IWAENC 2006, 2006)
In this paper we describe a novel algorithm for postprocessing a microphone array’s beamformer output to achieve better spatial filtering under noise and reverberation. For each audio frame and frequency bin the algorithm estimates the spatial probability for sound source presence and applies a spatio-temporal filter towards the look-up direction. It is implemented as a real-time post-processor after a time invariant beamformer and it substantially improves the directivity of the microphone array. The algorithm is CPU efficient and adapts quickly when the listening direction changes. It was evaluated with a linear four element microphone array. The directivity index improvement is up to 8 dB, the suppression of a jammer 40° from the sound source is up to 17 dB.